Inflation-predictable behavior and co-eruption deformation at Axial Seamount - Nooner, Scott L; Chadwick Jr., William W (SCIENCE, 2016)
Deformation of the ground surface at active volcanoes provides information about magma movements at depth. Improved seafloor deformation measurements between 2011 and 2015 documented a fourfold increase in magma supply and confirmed that Axial Seamount's eruptive behavior is inflation-predictable, probably triggered by a critical level of magmatic pressure. A 2015 eruption was successfully forecast on the basis of this deformation pattern and marked the first time that deflation and tilt were captured in real time by a new seafloor cabled observatory, revealing the timing, location, and volume of eruption-related magma movements. Improved modeling of the deformation suggests a steeply dipping prolate-spheroid pressure source beneath the eastern caldera that is consistent with the location of the zone of highest melt within the subcaldera magma reservoir determined from multichannel seismic results.
Keywords: AUV Sentry (Autonomous Underwater Vehicle); ROV Jason (Remotely Operated Vehicle)